A Case-Control Study on Risk Factors for Early Dental Implant Failure in Smokers and Non-Smokers - Awais Hussain, Usman Manzoor Warraich, Maha Maqbool, Ahmad Danyal, Mehreen Khaliq, Taif Ahmad, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
A case-control study evaluated risk factors associated with early dental implant failure in smokersversus non-smokers. Seventy patients with early failure (implant loss or mobility within 12months) were matched by age and implant site to 140 controls with successful implants at 12months. Baseline data included smoking status